Effects of stretching on molecular transfer from cell membrane by forming pores. Issue 4 (2nd October 2019) - Hadi, Amin; Rastgoo, Abbas; Bolhassani, Azam; Haghighipour, Nooshin
ABSTRACT: Cell function was incessantly regulated by several microenvironments that were dependent on chemical and physical interactions. Physical forces, such as compressive stress, shear stress, and tensile forces, were transduced to biochemical signals through a multistep mechanotransduction process. Cell membrane proteins, such as cell membrane transporters and focal adhesions, cytoskeletal networks, and the cell membrane lipid bilayer, were among the primary targets for mechanical stimuli. Mechanical stretching was studied and applied for regenerative medicine and cellular therapies. To divulge the stretch loading's working mechanism, a molecular dynamics simulation was conducted to apply the stretch loading to a 10 × 10 nm 2 phosphatidylcholine (POPC) membrane bilayer. For this purpose, the LAMMPS computational package was used for implementing simulations. Under this state of mechanical loading, the electrical property alterations in the phospholipid bilayer (outer surface) and the membrane pore formation were studied. To validate the data that were obtained from the simulations, an experiment was designed to assess gene transfection in cells under the application of stretch loading. The pEGFP-N1 plasmid, encoding the Green Fluorescent Protein (GFP), is utilized as the gene transfection marker. The molecular dynamic results show that the stretch loading engendered a change in the membrane electrical charge; changes the outer surface charges of the phospholipid bilayer from negative to positive. In addition, the results indicate that mechanical stretching was involved in creating cell membrane pores. The experimental data confirmed the exclusive effect of mechanical stretch on the delivery of negatively charged DNA plasmid into the living cells. These results suggest that the electrical alteration at the membrane interface played an imperative role in the mechanotransduction downstream physiological responses.